Historical cartography in Belarus (studies on the administrative division, borders and population of the Grand Duchy of Lithuania) - Vitsko, Dzmitry (Studia Geohistorica, 2019)
In Belarus, the historical geography is a relatively new and slowly developing discipline. It is widely acknowledged that its founder was Mikhail Spirydonau as he was the author of the first, published in 1993, detailed map of the Grand Duchy of Lithuania after signing the Union of Lublin, as well as the maps of particular districts. It was he who laid the foundations of the discipline and his maps are at the core of entire body of the geohistorical knowledge on The Grand Duchy of Lithuania. In the following years, the researchers Viachaslau Nasievich, Viktar Ciemushau, Andrei Miacielski and others had introduced into the scientific literature a great amount of data on the history of borders and population of the GDL, though the article only lists those works which contain maps or other cartographic editions. A number of historical atlases were also published, the most important of which is the ‘Great Historical Atlas of Belarus’ edited by V. Nasievich. The eastern border of the Grand Duchy of Lithuania in the 14th until the first half of the 16th c. was the subject of studies by V. Ciemushau. Currently, despite a great number of elaborated and published maps and atlases, the publications still lack works on historical geography, which would tackle and justify the administrative borders of the GDL and which would depict its settlement network. Such works present a great challenge, as this most important period covers over half of the millennium of Belarusian history. AA typical disquisition on the history of a particular administrative unit, which is a district, since it origins until its end in the 18th c. is seen as the most desirable scientific approach to the topic. It can be achieved by studying the population and the borders of particular estates (the ones at the borders of the neighbouring districts in particular). The work which is the closest to this model is the monograph by A. Miacielski on the Principality and Voivodship of Mstsislaw.